Historical waterfront of Rio de Janeiro: Cartography of landfills and new rehabilitation perspectives of the port area - Izaga, Fabiana Generoso de; de Silveira, Amanda Barbosa (International Planning History Society Proceedings, 2018)
This article seeks to analyse recent urban transformations and the conceptual bases that have been in force in the Urban Rehabilitation Project of Rio de Janeiro's waterfront. An attempt is made at establishing a connection between the development of the area, the evolution of the city's history, the activities carried out at the port, an its conversion to new uses. An analysis of the spatial transformations is done, especially in the 7-year (2009-16) span of the initial implementation of the ongoing ‘Porto Maravilha’ [Marvel Port] urban project, with the mapping of new and old urban fabric and infrastructure; bibliographical research on historiographical studies, city administration players, and technicians to unveil processes that concern urban projects as contemporary tools for land valuation. As a conclusion, we point that despite the major work recently carried out as a product of the Urban Operation Consortium Law guidelines, only 9% of the urban land stock has been negotiated, contradicting even the pessimistic forecasts of 50%. The area lacks an Integrated Urban Plan with a public policy approach, especially to foster housing as a key element for liveable neighbourhoods and a stronger connection with the green infrastructure of the Guanabara Bay ecosystem.